2003
DOI: 10.1111/1467-7687.00257
|View full text |Cite
|
Sign up to set email alerts
|

Children's understanding of the earth in a multicultural community: mental models or fragments of knowledge?

Abstract: Children's understanding of properties of the earth was investigated by interviewing Asian and white British classmates aged 4−8 years (N = 167). Two issues were explored: whether they held mental models of the earth (Vosniadou & Brewer, 1992) or instead had fragmented knowledge (di Sessa, 1988); and the influence of the children's different cultural backgrounds. Children selected from a set of plastic models and answered forced‐choice questions. Using this methodology, there were no significant differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
100
5
22

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(134 citation statements)
references
References 19 publications
7
100
5
22
Order By: Relevance
“…Siegal et al, 2004;Vosniadou, Skopeliti & Ikospentaki, 2004) are based on interviews, drawings and open-ended questions. On the other hand, research evidence based on 3D models or pictures selection tasks and forced-choice questions advocates the fragmented knowledge (Nobes et al, 2003(Nobes et al, , 2005Panagiotaki et al, 2006;Siegal et al, 2004;Straatemeier et al, 2008).…”
Section: Methodological Considerations: the Latent Class Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Siegal et al, 2004;Vosniadou, Skopeliti & Ikospentaki, 2004) are based on interviews, drawings and open-ended questions. On the other hand, research evidence based on 3D models or pictures selection tasks and forced-choice questions advocates the fragmented knowledge (Nobes et al, 2003(Nobes et al, , 2005Panagiotaki et al, 2006;Siegal et al, 2004;Straatemeier et al, 2008).…”
Section: Methodological Considerations: the Latent Class Analysismentioning
confidence: 99%
“…Using similar research tools, contemporary research in the same field of pupils' mental models has shown that the proposed models, initial and synthetic, although the most prevalent, are not the only ones and many variations are reported across cultures (Nobes, Moore, Martin, Clifford, Butterworth, Panagiotaki & Siegal, 2003;Samarapungavan, et al, 1996). Thus, some of the cross-cultural studies provided clues of inconsistent knowledge, shifting towards the 'fragmented knowledge perspective'.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Täiskasvanute mitu korda esitatud küsimused (sama asja kohta, kuid vähemalt täiskasvanu arvates natuke teise nurga alt) ajavad lapsi segadusse -nad võivad hakata kunstlikult uusi vastusevariante otsima. Lapsed ei suuda vastata üldistele ja abstraktsetele küsimustele, kuid konkreetsed küsimused on tihti liiga suunavad ja sunnivad lapsi mõtlema teatud suunas (Nobes & Moore & Martin et al 2003).…”
Section: Esmased Teadmisedunclassified
“…Eelkooliealiste laste esmastest astronoomiaalastest teadmistest pole ühtset arusaama (vrd Kikas 2003;Nobes & Moore & Martin et al 2003;Vosniadou & Brewer 1992 Integreeritud astronoomiaalaseid teadmisi ja mudeleid kirjeldab Stella Vosniadou oma kolleegidega. Nad on viinud läbi uurimusi mitmetes maades ja leidnud algseid Maa mudeleid ja sellele vastavaid seletusi ööpäeva ja aastaaegade vaheldumise kohta, mis on erinevates kultuurides suhteliselt sarnased (Diakidoy & Vosniadou & Hawks 1997;Samarapungavan & Vosniadou & Brewer 1996;Vosniadou & Brewer 1992.…”
Section: Esmased Teadmised Maast Ja Taevastunclassified